Cover Image. Issue 10 (14th June 2020) - Yang, Yang; Tam, Fred; Graham, Simon J.; Sun, Guochen; Li, Junjun; Gu, Chanyuan; Tao, Ran; Wang, Nizhuan; Bi, Hong‐Yan; Zuo, Zhentao
Abstract : COVER ILLUSTRATION Handwriting, a unique form of language and motor processing, has been found to show robust sex differences. Using fMRI, the neural evidence for the sex differences in handwriting was revealed. Specifically, males and females showed significant differences in brain activation and functional connectivity in Exner's area (illustrated as green circle), a writing‐specific brain region.